ABKHAZIA, KOSOVO AND THE RIGHT TO EXTERNAL SELF-DETERMINATION OF PEOPLES - SIDDI, Marco (CENTRAL ASIA AND THE CAUCASUS, 2011)
On 26 August 2008 the Russian Federation recognized the independence of Georgia’s breakaway provinces of Abkhazia and South Ossetia. In the statement that explained the reasons for Russia’s recognition, President Dmitry Medvedev referred to the “freely expressed will of the Abkhaz and Ossetian peoples” and to several fundamental international instruments that stress inter alia the principle of self-determination of peoples, notably the U.N. Charter, the 1970 U.N. General Assembly Declaration on Principles of International Law Concerning Friendly Relations and Cooperation among States (U.N. General Assembly Resolution 2625) and the 1975 Helsinki Final Act of the Conference on Security and Cooperation in Europe (CSCE). Medvedev also specified that Abkhazians and South Ossetians had the right to decide their destiny by themselves in the light of Georgia’s allegedly genocidal policies in South Ossetia and the existence of similar plans for Abkhazia.1 Therefore, in the August 2008 crisis Russia supported the controversial principle of external self-determination of peoples in exceptional circumstances, which it had fiercely opposed until then, most notably in the case of Kosovo’s declaration of independence. External self-determination implies “the right of every people to choose the sovereignty under which they live”. The concept of external self-determination is broader than that of internal self-determination, which refers primarily to “the right of peoples to select their own form of government” within a sovereign state.2 Internal self-determination thus concerns the granting of minority rights, regional autonomy regimes or federalism within an existing state. On the other hand, external self-determination refers in particular to the right to establish an internationally recognized independent state to represent a people. In other words, external self-determination implies the separation of a sub-group of a state with the consent of the central government, or its secession without the consent of the state concerned, and the establishment of a new state. Considering that international law is dominated by sovereign states and that secession poses a threat to their territorial integrity, the principle of external self-determination constitutes a very controversial issue.